Error and modification in thermal barrier coatings measurement using impedance spectroscopy. Issue 6 (15th April 2017) - Yang, L.; Zhu, W.; Li, C.F.; Zhou, Y.C.; Wang, N.G.; Wei, Y.G.
Abstract: In impedance spectroscopy testing of metal/ceramic multi-layers, such as thermal barrier coatings (TBCs), in order to avoid electric leakage, asymmetric electrode is widely adopted. However, how is electric field distribution in asymmetric electrode system, what error does it bring to measurement results, and how to modify these errors etc., are still not understood. In this study, electric field divergence in TBCs measurement induced by asymmetric electrode is investigated through solving a three-dimensional electric field equations numerically. The results show that the asymmetric electrode inevitably triggers divergence of electric field line, and as frequency decreases the divergence increases considerably. When Pt electrode diameter is chosen as 1 mm in ceramic coating, the errors in thickness measurement for both YSZ and TGO are 26.20% and 89.3%, respectively. The errors rise as both YSZ and TGO thicknesses increase, while the errors decrease as Pt electrode size increases. The error in thickness measurement for TGO layer is much larger than that for YSZ. Through present research, a scheme to eliminate the effect of electric field divergence on measurement error is proposed.